Open Online Education – Virtual Classrooms Open to Everyone - Varkonyi, Irvin (Defense Transportation Journal, 2018)
According to Wikipedia, a MOOC is an online course aimed at unlimited participation and open access via the web. Offerings have since expanded to include specializations-collections of courses that build skills in a specific subject-as well as degrees and a workforce development product for businesses and government organizations. * Udemy.com - An online learning platform, Udemy is aimed at professional adults. First and foremost, you should be digitally literate to best be able to work in the online environment.